If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + 2z + -1x = 0 Reorder the terms: -1x + 4y + 2z = 0 Solving -1x + 4y + 2z = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4y' to each side of the equation. -1x + 4y + -4y + 2z = 0 + -4y Combine like terms: 4y + -4y = 0 -1x + 0 + 2z = 0 + -4y -1x + 2z = 0 + -4y Remove the zero: -1x + 2z = -4y Add '-2z' to each side of the equation. -1x + 2z + -2z = -4y + -2z Combine like terms: 2z + -2z = 0 -1x + 0 = -4y + -2z -1x = -4y + -2z Divide each side by '-1'. x = 4y + 2z Simplifying x = 4y + 2z
| 16t^2+8t-80=0 | | 3(9a-6)= | | 5(8b+10)= | | -(6x-(2x+9))=-4-(6(2x-4)-6x) | | 7(5+y)= | | 25/60=5/15 | | 1.2x+3.8=8.696 | | 4(c-9)=-24 | | Q=1640-20p | | 10x+9=2x+25 | | 37x+5=y | | q+72=36 | | -y=5x+7 | | 2/5x-12/5 | | x+2x+3x-3-8=6x-11 | | 5(3h+-2)=2(h+8) | | -108+72=36 | | 110=(5a+6a) | | X-18=11x-38 | | 8(6u+5)= | | 6(2+a)=-18 | | 45=9q | | 25x^9/5x^8 | | x+y+z+t+u=7 | | 5(9+7y)= | | x+y+z+t=5 | | 35+25=40x | | -5(x/100-5x)=-2 | | 32f+26f=232 | | 45/x=18 | | 15c-6=24 | | 140=0.66666666666667c |